THEORETICAL AND METHODOLOGICAL BASIS OF THE FUNCTIONING OF COURSES OF ACADEMIC DISCIPLINES IN THE DISTANCE LEARNING SYSTEM OF HIGHER MILITARY EDUCATIONAL INSTITUTIONS - Oliynyk, Leonid; Aksanov, Timur (Distance Education in Ukraine: Innovative, Normative-Legal, Pedagogical Aspects, 2025)
The which is based on the analysis of the experience of distant from of tutoring the introduction in the national and international system of education, suggested the scientific theoretical and methodological substantiation of the creation and introduction of the educational course in the distant tutoring system from its application in the highest educational establishments.